Identification of diabetic nephropathy-selective proteins in human plasma by multi-lectin affinity chromatography and LC-MS/MS - Ahn, Jung-Mo; Kim, Byung-Gyu; Yu, Myong-Hee; Lee, In-Kyu; Cho, Je-Yoel (WILEY-V C H VERLAG GMBH, 2010)
Purpose Diabetic nephropathy (DN) is a serious complication of diabetes mellitus. Microalbuminuria has been established as a risk factor for the development of diabetic renal disease. Recently, microalbuminuria has been reported to have limitations in determining disease risk and predicting DN Therefore, identification of more specific biomarkers for prediction of DN is needed. Experimental design. When kidney damage is initiated, glycoprotein leakage into the blood may occur, thus altering the glycoproteome profile of the blood. Here, we have used a combined approach of glycoprotein enrichment of plasma with a proteomic analysis to discover potential DN biomarkers. We isolated glycoproteins from plasma provided by six type 2 diabetes control (DC) and six type 2 DN patients using multi-lectin affinity chromatography. Captured glycoproteins were resolved by 1-D PAGE and tryptic digests of isolated proteins were analyzed by LC-MS/MS. Results: From the comparative and semi-quantitative proteome analysis, we identified 13 up- and 14 down-regulated glycoproteins in DN plasma. Among the up-regulated glycoproteins, the levels of lumican, vasorin and retinol binding protein-4 were verified by Western blot analysis of individual plasma samples. Conclusion and clinical relevance. Collectively, our findings show that biomarker discovery has considerable potential for predicting diabetic nephropathy in diabetic patients.